Al-Qur’an dan Worldview Keagamaan Baru (Holistik, Rekonsiliatif, dan Mediatif) - Huda, Moh. Miftakhul (Lembaga Yasin AlSys, 2025)
The Qur'an, as the last revelation revealed to the Prophet Muhammad SAW, has a very wide role in the lives of Muslims. Apart from being a guideline for worship, the Qur'an also serves as a source of law, ethics, and guidance in living social, political, and cultural life. Along with the development of the times and the complexity of global problems, there is a need to understand the Qur'an through a new religious worldview that is more holistic, reconciliatory, and mediating. A holistic approach integrates the teachings of the Qur'an in all aspects of life, including morality, social, political, and ecological. The reconciliation approach aims to promote peace and conflict resolution both between individuals and between religious communities, prioritizing the values of tolerance and harmony. Meanwhile, the mediation approach directs the Qur'an as a bridge that connects differences, both in the internal context of Muslims and in dialogue between religious communities. This research aims to explore and analyze these three approaches in order to provide new insights in interpreting the teachings of the Qur'an in the era of globalization and plurality. With this approach, it is hoped that the Qur'an can contribute to creating a more peaceful, just, and harmonious world, as well as relevant in facing the challenges of the times.